WHO decides on the exception? Securitization and emergency governance in global health - Tine Hanrieder; Christian Kreuder-Sonnen (Security Dialogue, 2014)
This article analyses the emergency governance of international organizations by combining securitization theory with legal theory on the state of exception. Our main argument is that where issues are securitized as global threats, exceptionalism can emerge at the level of supranational bodies, endowing them with the decisionist authority to define emergencies and guide political responses. We theorize the `emergency trap', which is triggered when the emergency powers of international organizations reduce the obstacles to, and increase the incentives for, the securitization of further issues. Based on the idea that the emergency trap functions as an institutional driver of securitization, we also highlight the importance of the constitutional containment of emergency competencies as an alternative to discursive desecuritization strategies. We illustrate this security–emergency dynamic in a case study of the recent empowerment of the World Health Organization (WHO) in the governance of global health emergencies. The article shows how WHO's exceptional response to the 2003 severe acute respiratory syndrome (SARS) crisis paved the way for an institutionalization of emergency powers within the organization and contributed to securitizing the 2009 swine influenza outbreak as a global pandemic. However, WHO's crisis governance has also triggered internal and external processes of constitutional contention.
urn:nbn:de:bvb:19-epub-59041-5; Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation).
Keywords: 330; constitutional theory; Copenhagen School; exception; global health; international organizations; securitization; World Health Organization